Ferrovias, doenças e medicina tropical no Brasil da Primeira República Railroads, disease, and tropical medicine in Brazil under the First Republic - Jaime Larry Benchimol; André Felipe Cândido da Silva (História, Ciências, Saúde: Manguinhos)
Aborda o impacto da malária no âmbito da modernização republicana, basicamente nas ferrovias, que asssumiram então o papel de integrar o território e operar a expansão simbólica e material da nação brasileira. Os cientistas destacados para debelar os surtos epidêmicos não se limitaram a realizar as campanhas. Fizeram observações sobre aspectos da doença, inclusive suas relações com hospedeiros e ambientes, contribuindo com novos conhecimentos e com a institucionalização, no Brasil, de novo campo que então se estabelecia nas potências coloniais européias: a medicina tropical. O artigo articula essas inovações - especialmente a teoria da infecção domiciliária - com as campanhas em prol de ferrovias e com estágio subseqüente no enfrentamento da malária no Brasil, nos anos 1920. The article explores the impact of malaria on infrastructure works - above all, railroads - under the republican drive towards modernization. Railways helped tie the territory together and foster the symbolic and material expansion of the Brazilian nation. The scientists entrusted with vanquishing such epidemic outbreaks did not just conduct campaigns; they also undertook painstaking observations of aspects of the disease, including its relations to hosts and the environment, thus contributing to the production of new knowledge of malaria and to the institutionalization of a new field in Brazil, then taking root in Europe's colonies: "tropical medicine." The article shows the ties between these innovations (especially the theory of domiciliary infection) and the sanitary campaigns that helped the railways, which in the 1920s were followed by a new phase in Brazil's anti-malaria efforts.